The International Guidelines on HIV/AIDS and Human Rights--three years on - Patterson, D (Canadian HIV-AIDS policy & law newsletter, 1999)
1999 was the third anniversary of the drafting of the International Guidelines on HIV/AIDS and Human Rights. This article reviews the history of the Guidelines, notes some obstacles to their implementation, and concludes with suggestions for governments and development agencies